Ocena funkcji barku u pacjentek po 50 r.ż. z objawem łopatki skrzydlatej, oraz bez tej dysfunkcji, leczonych z powodu raka piersi. Badanie przekrojowe = Assessment of shoulder function in patients 50 years of age treated for breast cancer. Cross-sectional study - Włoch, Anna; Ridan, Tomasz; Opuchlik, Anna; Widłak, Patrycja; Kamińska-Gwóźdź, Ewelina; Krupnik, Szymon (Journal of Education, Health and Sport, 2016)
Włoch Anna, Ridan Tomasz, Opuchlik Anna, Widłak Patrycja, Kamińska‑Gwóźdź Ewelina, Krupnik Szymon. Ocena funkcji barku u pacjentek po 50 r.ż. z objawem łopatki skrzydlatej, oraz bez tej dysfunkcji, leczonych z powodu raka piersi. Badanie przekrojowe = Assessment of shoulder function in patients 50 years of age treated for breast cancer. Cross-sectional study. Journal of Education, Health and Sport. 2016;6(2):190-199. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46409 http://ojs.ukw.edu.pl/index.php/johs/article/view/3388 https://pbn.nauka.gov.pl/works/716361 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016. Praca oryginalna The original work Ocena funkcji barku u pacjentek po 50 r.ż. z objawem łopatki skrzydlatej, oraz bez tej dysfunkcji, leczonych z powodu raka piersi. Badanie przekrojowe Assessment of shoulder function in patients 50 years of age treated for breast cancer. Cross-sectional study Włoch Anna1,2, Ridan Tomasz3, Opuchlik Anna1,4, Widłak Patrycja5, Kamińska‑Gwóźdź Ewelina2, Krupnik Szymon6 1Świętokrzyskie Centrum Onkologii, Zakład Rehabilitacji, Kielce 2Uniwersytet Jana Kochanowskiego w Kielcach, Wydział Lekarski i Nauk o Zdrowiu, Instytut Fizjoterapii 3Akademia Wychowania Fizycznego w Krakowie, Wydział Rehabilitacji Ruchowej, Katedra Fizjoterapii, Zakład Kinezyterapii 4Wszechnica Świętokrzyska w Kielcach Zdrowiu, Wydział Wychowania Fizycznego i Turystyki, Katedra Fizjoterapii 5Uniwersytet Medyczny w Łodzi, Klinika Rehabilitacji i Medycyny Fizykalnej 6Akademia Wychowania Fizycznego w Krakowie, Wydział Rehabilitacji Ruchowej, Studia Doktoranckie Wloch Anna1,2, Ridan Tomasz3, Opuchlik Anna1,4, Widlak Patrycja5, Kaminska‑Gwozdz Ewelina2, Krupnik Szymon6 ¹ Holy Cross Cancer Center, Rehabilitation Department, Kielce, Poland 2 Jan Kochanowski University in Kielce, Medicine and Health Science Department, Poland 3 University School of Physical Education, Department of Physical Rehabilitation, Al. Jana Pawła II 78, PL-31-571 Krakow, Poland 4 Holy Cross University in Kielce, Department of Physical Education and Tourism, Poland 5 Medical University of Lodz, Clinic of Rehabilitation and Physical Medicine, Poland 6 University School of Physical Education, Department of Sport, Al. Jana Pawła II 78, PL-31-571 Krakow, Poland Adres do korespondencji: dr n med. Włoch Anna Świętokrzyskie Centrum Onkologii, Zakład Rehabilitacji. Artwińskiego 3, 25-734 Kielce Tel/Fax. 41 367 4168 Email: annawloch@onet.eu Słowa kluczowe: rak piersi, zakres ruchomości, bark, siła mięśniowa, łopatka skrzydlata, starsi dorośli. Key words: breast cancer, range of motion, shoulder, strength, winged scapula, older adults. Wprowadzenie i cel pracy: Około 70 tysięcy kobiet w Polsce, żyje z co najmniej pięcioletnią,zdiagnozowaną chorobą nowotworową piersi.Od 40 do 60 % badanych, 12 miesięcy po leczeniu operacyjnym oraz uzupełniającym,posiada przynajmniej jeden problem funkcjonalny barku, który może wynikać z współwystępowania łopatki skrzydlatej.Celem badania była ocena funkcji barku w ruchach wykonywanych w stawie ramienno-łopatkowym oraz barkowym (u pacjentek z grupy wiekowej 50-59 lat z objawem łopatki skrzydlatej po lewej stronie ciała,która została objęta zabiegiem chirurgicznym. Materiał i Metody: Materiał zebrano w Zakładzie Rehabilitacji Świętokrzyskiego Centrum Onkologii w Kielcach. Kryteria włączenia (wiek, płeć, leczenie w Świętokrzyskim Centrum Onkologii, >2 lata od zabiegu), spełniło 32 pacjentki po 50. roku życia.Goniometrem wykonano pomiar zakresu ruchomości w stawie ramienno-łopatkowym,antropomentrem zbadano zakres ruchomości barku.Dynamometrem zbadano siłę wybranych grup mm. barku podczas unoszenia, wysuwania do przodu oraz cofania. Wyniki: Ruchomość stawu ramienno-łopatkowego po mastektomii lewej piersi,była istotnie statystycznie ograniczona w ruchach zgięcia(9°),wyprostu pionowego(5°), odwodzenia(8,2°),rotacji wewnętrznej(3,4°) oraz rotacji zewnętrznej(10,9°) w porównaniu do strony zdrowej u tych samych pacjentek. Siła mięśniowa w wybranych grupach mięśni barku różniła się istotnie statystycznie pomiędzy kończyną górną objętą mastektomią z objawem skrzydlatej a kończyną zdrową tych samych pacjentek. Wnioski Ruchomość stawu ramienno-łopatkowego,u pacjentek w grupie 50-59 lat po mastektomii z objawem łopatki skrzydlatej różni się wartością zgięcia w porównaniu do pacjentek po mastektomii bez tego objawu. Siła mięśniowa w wybranych ruchach barku nie różni się pomiędzy pacjentkami po mastektomii z objawem łopatki skrzydlatej,a badanymi po mastektomii bez tego objawu. Introduction and purpose: Approximately 70,000 women in Poland, lives with at least five years, diagnosed with breast cancer. 40 to 60% of the respondents, 12 months after surgery and adjuvant therapy, has at least one functional problem of the shoulder, which may result from the co-existence winged scapula. Aim of the study was to evaluate the function and range of motion of the shoulder (in patients from the age group 50-59 years, symptom winged shoulder on the left side of the body, which has been acquired surgery). Material and Methods: The material collected in the Department of Rehabilitation Holy Cross Cancer Center in Kielce. Inclusion criteria (age, sex, treatment at Holy Cross Cancer Center > 2 years after surgery), met 32 patients over 50 years of age. Goniometric assessment made to measure range of motion in the joint, Anthropometric examined the range of motion of the shoulder. Dynamometer was used to assess the strength of selected muscle groups while lifting, protract and retract of the shoulder. Results: The mobility of glenohumeral and scapular joint on the left breast mastectomy was significantly restricted in the movements of flexion (9°), vertical extension (5°), abduction (8.2°), internal rotation (3.4°) and external rotation (10.9°) compared to the healthy side in the same patients. Muscle strength in selected groups of shoulder muscles differed significantly between the upper limb covered mastectomy with symptom winged scapula and healthy limb of the same patients. Conclusion 1. Mobility of the shoulder patients in the group of 50-59 years after mastectomy symptom winged blades vary the value of bending compared to patients after mastectomy without this symptom. 2. The strength of muscle movements in the selected shoulder does not differ between patients after mastectomy symptom winged blade, and tested after mastectomy without symptoms.